2022
DOI: 10.3389/fimmu.2022.937201
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dyslipidemia and inflammation among adults in east coast China: A cross-sectional study

Abstract: ObjectiveDyslipidemia is one of the major public health problems in China. It is characterized by multisystem dysregulation and inflammation, and oxidant/antioxidant balance has been suggested as an important factor for its initiation and progression. The objective of this study was to determine the relationship between prevalence of dyslipidemia and measured changes in the levels of proinflammatory cytokines (IL-6, TNF-a, and MCP-1), thiobarbituric acid-reactant substances (TBARS), and serum total antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Patients with dyslipidemia tend to have high levels of in ammation and lipid disorders, which are key risk factors for human atherosclerosis and thrombosis, as well as important risk factors for cardiovascular disease (29)(30)(31). Previous studies have shown that DPA could adjust in ammation and blood lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with dyslipidemia tend to have high levels of in ammation and lipid disorders, which are key risk factors for human atherosclerosis and thrombosis, as well as important risk factors for cardiovascular disease (29)(30)(31). Previous studies have shown that DPA could adjust in ammation and blood lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus was defined as glycosylated Hb (HbA1c) ≥ 6•5 %, fasting blood glucose ≥ 7•0 mmol/l or taking hypoglycaemic medications (21) . Dyslipidaemia was defined as TC ≥ 5•18 mmol/l, or (and) TG ≥ 1•7 mmol/l, or (and) LDL-cholesterol ≥ 3•37 mmol/l, or (and) HDL-cholesterol < 1•04 mmol/l or taking lipid-lowering drugs (22) .…”
Section: Definition Of Covariatesmentioning
confidence: 99%
“…Excess ROS depletes antioxidant defenses and activate nuclear factor‐kB, resulting in pro‐inflammatory cytokines release that can further increase ROS and together provoke cell death. Pro‐inflammatory cytokines have been shown to influence abnormalities in lipid metabolism in atherosclerosis, obesity, steatosis, and diabetes (Hong et al, 2022; Popko et al, 2010). Therefore, agents with antihyperlipidemic, antioxidant, and anti‐inflammatory activities could effectively manage dyslipidemia and prevent its associated complications and disorders.…”
Section: Introductionmentioning
confidence: 99%